Experimental study and field application of hydraulic flushing technology in soft coal seam - Xun Zhao; Bei Hu; Baisheng Nie; Xianfeng Liu; Dan Zhao; Hongsheng Li; Chuan Deng; Zhengpeng Duan (Scientific Reports)
Abstract To enhance the safety of coal mining operations and improve the efficiency of gas extraction, hydraulic flushing technology has been widely used in low permeability coal seams. This study aims to investigate the mechanism of hydraulic flushing by conducting experiments focusing on four aspects: sample strength, punching pressure, punching position and vibration direction. The results show that an increase in hydraulic flushing pressure leads to a deeper impact groove, whereas higher sample strength results in a shallower groove. Additionally, the amplitude of stress wave is positively correlated with the density of the sample, with low-strength samples exhibiting extensive stress wave propagation and minimal attenuation. The stress wave vibration is multi-directional, which can maximize the instability and destruction of the internal structure of the coal body. To validate the practical efficacy of hydraulic flushing, a field test was conducted at the Yuwu Coal Mine in Changzhi City, Shanxi Province. The field trial shows that the effective influence radius of hydraulic flushing can reach 4 m, with a significantly lower gas flow attenuation coefficient compared to ordinary borehole. Notably, the permeability of coal seam in hydraulic flushing area is close to twice that of ordinary drilling area.